2017
DOI: 10.12669/pjms.332.11854
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of nutritional anemia among female medical students of Faisalabad

Abstract: Background and Objective:Anemia is a common health problem worldwide. This problem is most commonly faced by 18 to 25 years of females. Medical students especially female hostelites poses high risk of anemia because of their poor eating habits, breakfast skipping, long schedule in college, burden of medical studies, clinical postings, and extra-curricular activities. Therefore the current study was designed to determine the hemoglobin status in young female medical students. We also elucidate its association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
0
17
1
4
Order By: Relevance
“… 8 Various studies reported higher frequency of anaemia among underweight females in Pakistan. 4 Surprisingly, anaemia among obese FMS was more frequent in present study supported by negative relation between Hb and BMI in total FMS(data not displayed). It seems that dietary diversity did not affect the anaemia status of obese FMS.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“… 8 Various studies reported higher frequency of anaemia among underweight females in Pakistan. 4 Surprisingly, anaemia among obese FMS was more frequent in present study supported by negative relation between Hb and BMI in total FMS(data not displayed). It seems that dietary diversity did not affect the anaemia status of obese FMS.…”
Section: Discussioncontrasting
confidence: 41%
“…Jawed, S. et al, reported 33% anaemia frequency in 2017 increasing up to 69% in 2018 among female medical student (FMS), thus emerging as a moderate to major public health problem. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Я часто відчуваю сонливість Я надаю перевагу проводженню вільного часу вдома У мене виникає задишка/відчуття неcтачі повітря при фізичному навантаженні Я швидко стомлююсь при фізичному навантаженні Мене іноді турбує біль в грудній клітці У закритому приміщенні мені не вистачає повітря / паморочиться в голові/ болить голова Я засинаю на уроках У мене тріскаються губи У мене іноді бувають «заїди»/ тріщини в кутках рота, які погано загоюються У мене ламке волосся У помічаю, що у мене випадає волосся У мене лущаться нігті Я їм м'ясо (рибу, бобові, яйця) рідше 1-2 разів на день Я п'ю каву/ зелений чай/ газовані напої Я маю гастрит/целіакію/часті розлади травлення В П О М О Щ Ь П Р А К Т И Ч Е С К О М У В Р А Ч У витку, але й може викликати хронічну втому, зумовлювати зниження імунітету, порушення роботи залоз внутрішньої секреції, нервової системи. З цим станом також пов'язане зниження ефективності праці і якості життя [1,2,5,6].…”
Section: я часто почуваюсь стомленим(ою)unclassified
“…Саме тому при формуванні державних програм зі скринінгу мають бути враховані всі аспекти -медичні, психологічні, соціально-економічні тощо, а обґрунтування вибору видів скринінгу повинно відбуватися на засадах доказової медицини [4,5,6].…”
unclassified
“…Anemia is mostly detected in the underweight females having body mass index (BMI) less than 18.5 kg/m 2 . Hence, it shows that the nutritional status has significant relationship with anemia in the young females (Jawed et al, 2017).…”
Section: Introductionmentioning
confidence: 95%